Association between Variation of Troponin and Prognosis of Acute Myocardial Infarction before and after Primary Percutaneous Coronary Intervention - Xiaoxiao Zhao; Ying Wang; Chen Liu; Peng Zhou; Zhaoxue Sheng; Jiannan Li; Jinying Zhou; Runzhen Chen; Yi Chen; Hanjun Zhao; Hongbing Yan (Journal of Interventional Cardiology)
Background. Circulating levels of cardiac troponin I (cTnI) after ST-segment elevation myocardial infarction (STEMI) were considered as prognostic factors for predicting the incidence of major adverse cardiovascular events (MACE). △cTnI is the difference between peak cTnI after primary percutaneous coronary intervention (PPCI) and cTnI on initial admission. Purpose. This study aimed to assess the relationship between △cTnI, the ratio of △cTnI to cTnI on initial admission, and the incidence of MACE during the follow-up period. Methods. A total of 2596 patients with cTnI measured upon admission and one-time measurement of cTnI during hospitalization were enrolled. Results. In the adjusted models of the survival receiver operating characteristic (ROC) curve, △cTnI and the ratio of △cTnI to cTnI on initial admission have stronger discrimination power of MACE (area under curve (AUC) 0.730 and 0.717) compared with peak cTnI after PPCI and cTnI at admission (AUC 0.590, 0.546). Multivariate Cox regression analysis identified △cTnI (hazard ratio (HR) 1.018, 95% confidence interval (CI) 1.001 to 1.035) as a relevant factor for MACE during follow-up. △cTnI was divided into quartiles, and maximum △ cTnI between 4.845 and 19.073 ng/ml comprised more patients with anterior wall myocardial infarction (p < 0.001), higher GRACE score (p = 0.038), CK-MB (p = 0.023), and Myoglobin (p < 0.001). On the K–M survival curves, the incidence of MACE, mortality, and angina pectoris were significantly higher in the group with maximum △cTnI (p = 0.035, 0.049, 0.026). Conclusion. The △cTnI level and the ratio of △cTnI have stronger discrimination power of predicting the incidence of MACE. The group with maximum △cTnI has higher incidence of MACE, mortality, and angina pectoris during the follow-up period.